Essentials of Regional Anesthesia - Kaye, Alan D.; Urman, Richard D.; Vadivelu, Nalini (Springer New York : Imprint: Springer, 2012)
This is a compact, single-source guide to regional anesthesia.  Chapters are authored by regional anesthesia fellowship directors and fellows to insure maximum practicality and up-to-date coverage.    Essentials of Regional Anesthesia covers all anatomical regions as well as the unique considerations in patients with chronic pain, obstetric patients, pediatric patients, and patients treated in the outpatient setting.   A common chapter format makes it easy to find information quickly, and extensive illustrations enhance the text.    Stay current with Essentials of Regional Anesthesia, and stay ahead with these helpful features: • Ultrasound incorporated into each block • Extremely practical focus • More than 400 Q & As to test knowledge • Authored by regional anesthesia fellowship directors and fellows • Clinical pearls and guidance on complications • Concise, clinically oriented review of relevant basic science • Common chapter format for ease of use • Well illustrated with 350 figures, nearly 200 in color.